Innovative Methods and Technologies of Learning in German Universities - Kh.R. Bobobekova; M.Kh. Nurullaeva (Global Scientific Publishing, 2023)
In Germany, educational curricula are set at the state-level, similar to the US and Canada. The German Schools Abroad in North America follow the German curriculum from the state of Thuringa, known for its high educational standards
Keywords: Flip the Classroom; personalized Learning; Project-Based Learning